Phage display–mediated immuno-PCR to detect low-abundance secreted proteins in Drosophila - Myeonghoon Han; Baolong Xia; Ah-Ram Kim; Elizabeth Filine; Emily Stoneburner; Ting Miao; Ying Liu; Jonathan Zirin; Norbert Perrimon (Proceedings of the National Academy of Sciences, 2026)
Circulating hormones, that mediate communications across organs to maintain physiological balance, are commonly detected and quantified using enzyme-linked immunosorbent assays (ELISAs). However, while ELISA is well suited for organisms where sample blood can be readily obtained, its application is considerably more challenging in smaller organisms, particularly Drosophila , which has gained widespread use in recent years for physiological studies. Here, we present sensitive phage display–mediated immuno-PCR (PD-iPCR) to detect Drosophila hemolymph proteins via two approaches: 1) by identifying high-affinity nanobodies through phage display library screening and subsequent affinity maturation and 2) by generating a knock-in fly line producing secreted proteins tagged with tandem NanoTags composed of VHH05 and 127D01. Using these approaches, we successfully established PD-iPCR to detect insulin-binding ImpL2 protein in fly hemolymph. Notably, the tandem NanoTag-based sandwich PD-iPCR enabled highly sensitive detection of tagged antigens, allowing us to quantify elevated ImpL2 levels in the hemolymph of starved flies and those bearing Yki -induced gut tumors. Collectively, our results demonstrate that PD-iPCR enables detection of endogenous, low-abundance circulating hormones in Drosophila , providing a powerful tool for studying interorgan communication.